EFFECT OF DIFFERENT BODY WEIGHT CATEGORIES ON THE PRODUCTIVE PERFORMANCE OF FOUR CLOSE-BRED FLOCKS OF JAPANESE QUAILS (Coturnix coturnix japonica) - A. S. Jatoi; A. W. Sahota; M. Akram; K. Javed; M. H. Jaspal; J. Hussain; A. H. Mirani; S. Mehmood (Journal of Animal and Plant Sciences, 2013)
A study was conducted to investigate the effect of different body weight categories on productive performance of four close-bred flocks of Japanese quails maintained at Avian Research and Training Centre, University of Veterinary and Animal Sciences, Lahore. For this purpose, a total of 432 adult (12 weeks-old) quails, comprising 108 males and 324 females were randomly divided into 108 experimental units, comprising one male and three females each. These experimental units were randomly assigned to 12 treatment groups having 4 close-bred flocks x 3 female body weights (heavy 300-350g, medium 250-300g and small 200-250g) with randomized complete block design in factorial arrangements having 9 replicates in each treatment. Significant differences were observed in mean body weight and egg weight among imported and all local flocks. Mean egg production percent, egg number, egg mass (g/bird) and FCR (g/egg) differed non-significantly among different close-bred flocks. With respect to body size categories, a significant (p<0.05) difference was observed in their mean body weight, egg number, egg weight and FCR (g/egg). However egg mass (g)/bird were found to be non-significant. Interaction between flocks and body sizes was significant in respect of all the above parameters. The average weekly body weight, egg weight and feed conversion ratio (g/g egg mass) in imported flock remained on higher side than that of local flocks. The heavy weight category birds had maximum body weight and egg weight followed by that of medium and small size groups. The average weekly egg production percent/bird, egg number and egg mass g/bird in the local-3 flock remained higher than that of imported, local-1 and 2 flocks. The small weight category birds had maximum egg production percent, egg number and egg mass g/bird than that of heavy and medium size. The average weekly FCR (g/egg) in local-1 flock remained on higher side than in the imported, local-2 and 3 flocks. The heavy weight category birds had maximum FCR (g/egg) than those from medium and small size birds.
Keywords: Body weight; egg production (egg number; egg weight; egg mass g/bird) and FCR/egg